New extensions of associated Laguerre polynomials - Ahmed Ali Al-Gonah (E-Journal of Analysis and Applied Mathematics)
The main object of this paper is to present new extensions of associated Laguerre polynomials. Some integral representations, recurrence relations, generating functions and summation formulae are obtained for these new extended Laguerre polynomials.